2008
DOI: 10.1080/09513590802302985
|View full text |Cite
|
Sign up to set email alerts
|

The vitamin D receptor geneBsmI polymorphism is not associated with anthropometric and biochemical parameters describing metabolic syndrome in postmenopausal women

Abstract: The BsmI polymorphism in the VDR gene does not seem to predispose to obesity and insulin resistance, but the BB genotype is connected with an unfavorable lipid profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 25 publications
6
19
1
Order By: Relevance
“…These studies support the notion that haplotype 1 may be associated with survival benefit, as was shown by a tendency in this study. Studies examining the associations between the BsmI, ApaI, and TaqI polymorphisms and cardiovascular risk factors, such as blood pressure and lipid profile, have shown conflicting results (8,15,38). In this study, the HR was not influenced by correction for several cardiovascular risk factors, suggesting that the effect is not mediated by these factors.…”
Section: Discussionmentioning
confidence: 49%
“…These studies support the notion that haplotype 1 may be associated with survival benefit, as was shown by a tendency in this study. Studies examining the associations between the BsmI, ApaI, and TaqI polymorphisms and cardiovascular risk factors, such as blood pressure and lipid profile, have shown conflicting results (8,15,38). In this study, the HR was not influenced by correction for several cardiovascular risk factors, suggesting that the effect is not mediated by these factors.…”
Section: Discussionmentioning
confidence: 49%
“…These consistent findings for Bsm I and obesity with the risk increasing allele being ‘A’ were confirmed when the phenotypes of interest were type 2 diabetes, fasting glucose level and CHD risk in recent studies ( 13 , 14 ) . In contrast, among 351 postmenopausal healthy women, VDR Bsm I polymorphism (‘A’ risk allele) was not associated with obesity or insulin resistance but was connected with an unfavourable lipid profile ( 36 ) . Additionally, a case–control study with 309 unrelated French subjects with type 2 diabetes, and among those with early onset in particular, the Taq I SNP (‘A’ allele) was associated with a higher BMI and an increased prevalence of obesity, compared with the controls ( 16 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Several recent cross-sectional and case–control studies have examined VDR genetic polymorphisms as potential risk markers for central adiposity and related metabolic disorders ( 9 11 , 16 , 17 , 36 , 37 ) . When testing VDR SNP associations with adiposity, a recent cross-sectional study (176 randomly selected men aged 25–65 years) found that homozygous BsmI (AA v. GG) was associated with higher BMI (29·0 v. 26·8 kg/m 2 ; P  = 0·024) and higher WC (101·8 v. 96·2 cm; P = 0·014) ( 11 ) .…”
Section: Discussionmentioning
confidence: 99%
“…VDR BsmI and FokI polymorphisms have been previously reported to be associated with anthropometric and biochemical parameters describing MS. Trzmiel et al (2008) found that VDR BsmI polymorphism seemed to influence BMI, while the FokI VDR polymorphism appeared to affect insulin sensitivity and serum HDL cholesterol in men [24]. However, Lwow et al (2008) indicated that VDR BsmI polymorphism did not seem to predispose postmenopausal women to obesity and insulin resistance, but the genotype BB was connected with dyslipidemia [30]. Frey et al (2003) did not find evidence for the association of VDR polymorphisms with glycemia either [31].…”
Section: Discussionmentioning
confidence: 99%